(untitled) (Academicia Globe: Inderscience Research, 2023)
Over the past decades, the unprecedented rate of global warming and climate change has been a source of concern. In recent years, climate change has been considered as one of the leading factors influencing public health and the formation of acute and chronic non-communicable diseases. The Fergana Valley of Kyrgyzstan belongs to a different climatic and geographical zone. Residents of the plains and low-mountain regions of southern Kyrgyzstan are more adapted to a hot climate, the effect of which on their health has not been studied using new WHO methodological approaches.